Portfólios na Educação Infantil: um projeto de intervenção fundamentado na ação formativa - Tonello, Denise Maria Milan (2015)
This research is based on a concern about the evaluation process in early childhood education and the way it is presented to parents. The predominant rating model in most institutions is characterized by the filling of records that have generic information, which creates, on the teacher, a feeling insufficiency because it fails to communicate the process of each student as something particular and unique. Thus, whatever the form of record may be, it does not seem to contemplate one of the main premises of assessment practices: the assessment for decision-making. In addition, the apparent lack of knowledge about the evaluation practices and its formative role generates a demand from educators and families, disregarding the procedural assessment of young children. Focused on training trainers, this research has two main objectives: first, it prepares a training course for teachers, proposing the use of portfolios as an assessment strategy of the learning process. this training course aims at promoting a reflective thinking on evaluation review and modify assessment practices in kindergarten, investigating the viewpoint of the teachers, the relevance of a training course in the daily work, and finally reelaborate with the teachers contribution, the initial training course, so that they would be able to replicated what they have learned to other teachers in order to promote a change on assessment practices of this initial stage of schooling. From the training point of view, this research is relevant, because in addition to encourage reflection on the role of evaluation and the development of portfolios as formative assessment instruments, it will contribute more assertively to create guidelines for teacher training courses